A Multicenter Randomized Controlled Pilot Trial Testing the Efficacy and Safety of Pterygopalatine Fossa Puncture Using One Acupuncture Needle for Moderate-to-Severe Persistent Allergic Rhinitis. (20th February 2020) - Zhang, Lu; Jiang, Lei; Cheng, Kai; Fu, Jian-Hua; Jian-Wu, Shen; Wang, Ke-Jian; Song, Yu-juan; Meng, Xian-zhong; Xu, Zhi-Xian; Chen, Li-He; Guo, Meng-Meng; Zhang, Li-juan; et al.
Abstract : Objective . To compare the efficacy and safety of pterygopalatine fossa puncture using one acupuncture needle inserted through the temporal fossa (intervention) and Chinese verum acupuncture (VA) in patients with moderate-to-severe persistent allergic rhinitis. Methods . The patients were randomized to an intervention group receiving pterygopalatine fossa puncture with one acupuncture needle for 4 weeks (once or twice weekly, 4–8 sessions in total, with a second course performed if required) or to a control group receiving individualized VA for 4 weeks (twice weekly, eight sessions in total). Patients were followed up 4 weeks later. Results . Ninety-six participants were assigned to intervention ( n  = 48) or VA ( n  = 48) groups. After treatment, differences in the total nasal symptom score (2004 Chinese version), total nonnasal symptom score, Rhinoconjunctivitis Quality of Life Questionnaire score, and symptomatic days were not significant between the groups (P > 0.05 in all cases). Compared with the VA, the time to onset of effect in the intervention group was shorter and the duration of effectiveness was longer. The mean clinical waiting time was significantly shorter in the intervention group than in the control group (6.640 ± 3.035 min and 31.19 ± 10.216 min, respectively). The total number of sessions in the VA group was 384; 7 episodes of subcutaneous bleeding occurred but did not require treatment. The total number of sessions in the intervention group was 185. Two cases of subcutaneous bleeding (one of local hematoma during the intervention and the other one of bruising in the palpebra inferior on the day after intervention) resolved upon withdrawal from the study. Conclusions . Pterygopalatine fossa puncture using one acupuncture needle resulted in a shorter time to onset of effect, a longer duration of effectiveness, and less clinical waiting time when compared with VA. Though the significant differences for TNSS and TNNSS were shown within intervention and VA groups, there were no differences between the two groups. Although the rate of subcutaneous bleeding was low, these adverse events may influence patient compliance. This trial is registered with ISRCTN21980724 .